If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + 7x = 72 Combine like terms: 6x + 7x = 13x 13x = 72 Solving 13x = 72 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Divide each side by '13'. x = 5.538461538 Simplifying x = 5.538461538
| (2+yi)*(x-3i)=7-i | | 13b=-12+16b | | 7+6(1w-3)=31 | | -v-10=10-6v | | 5j-10+9j=5+9j | | -14+3x=x | | 6a+7b=19 | | 3x-10=2x+20 | | 5(1a-4)=44 | | 4s=5s+6 | | 3(x-2)=2x+3+x | | X^2-25x+256=0 | | 18=2[x+6] | | 10p=6+7p | | 5x+50=-95 | | g+10=-9g | | a=15-b | | 8n-10=10n+10 | | x=-27+-2.25y | | ab=56 | | 3x-4+2y= | | 2(a-2)=49(2a-4) | | (2x+6)+(2x+5)+(2x)=(2x)+(2x)+(3x+2) | | -3q-8=10-5q | | -8z+8=-7z | | 1t^2-300t+45000= | | 8g+41=6g+95 | | 3(y+4)+2=29 | | 1.8+2.5= | | 4s-10=6s | | 4(5x+2)=Y | | 10-3u=-5u-4 |